2021
DOI: 10.3390/agronomy11112264
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Temperate Tannin Containing Forage Legumes to Improve Sustainability in Forage–Livestock Production

Abstract: Greenhouse gas emissions from ruminant livestock production systems contribute significantly to the environmental footprint of agriculture. Emissions are lower for feedlot systems than for grass-based systems primarily because of the extra time required for grass-finished cattle to reach slaughter weight. In contrast, legume forages are of greater quality than grasses, which enhances intake and food conversion efficiencies, leading to improvements in production and reductions in environmental impacts compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 166 publications
(226 reference statements)
0
8
0
Order By: Relevance
“…There it depends on the animal species (monogastric vs. ruminant animals), if certain amounts of antinutrients (even more individually for tannins) are compatible. 30,40 For example, Jansman et al reported that peas with a high tannin content reduced the protein digestibility for pig feeding and, respectively, increased the endogenous excretion of proteins, especially those that were rich in proline and histidine. 41 Tannins also showed a significant negative impact on apparent energy and protein digestibility in broiler feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There it depends on the animal species (monogastric vs. ruminant animals), if certain amounts of antinutrients (even more individually for tannins) are compatible. 30,40 For example, Jansman et al reported that peas with a high tannin content reduced the protein digestibility for pig feeding and, respectively, increased the endogenous excretion of proteins, especially those that were rich in proline and histidine. 41 Tannins also showed a significant negative impact on apparent energy and protein digestibility in broiler feeding.…”
Section: Discussionmentioning
confidence: 99%
“…There it depends on the animal species (monogastric vs . ruminant animals), if certain amounts of antinutrients (even more individually for tannins) are compatible 30,40 . For example, Jansman et al .…”
Section: Discussionmentioning
confidence: 99%
“…The PC/PD ratio can affect the biological activity of CTs, as demonstrated in sainfoin ( Onobrychis viciifolia ) (Hatew et al 2016 ). The degree of polymerization and cis/trans ratio also play a role in the biological activity of CTs, as shown by a negative correlation between nitrogen solubility and these factors in sainfoin (Lagrange et al 2021 ).…”
Section: Mechanisms Of Action and Catabolism Of Phytobiotic Additives...mentioning
confidence: 99%
“…Inclusion of bioactive forages, such as tannin containing forages, are deemed to be a particularly promising CH 4 mitigation strategy due to their concomitant reduction of food-feed competition, and their bene cial effects on animal health and productivity [7][8][9] . For example, the inclusion of tannin-containing forages in grasslandbased livestock production systems has the potential to reduce bloating incidences and parasitic burdens in animals 10,11 . The bene ts of tannins are derived from their molecular structure, which enables them to form stable complexes with both feed components (such as protein or ber) which can reduce the production of ammonia during ruminal fermentation and increase the fraction of rumen escape protein 12,13 .…”
Section: Introductionmentioning
confidence: 99%